2018
DOI: 10.1007/s00223-018-0488-z
|View full text |Cite
|
Sign up to set email alerts
|

Trabecular Bone Score (TBS) and Bone Metabolism in Patients Affected with Type 1 Neurofibromatosis (NF1)

Abstract: In patients with neurofibromatosis type 1 (NF1), decreased bone mineral density (BMD) and low levels of 25-hydroxy vitamin D3 (25OHD) have been reported. Recently, the trabecular bone score (TBS) measurement has been proposed as index of bone microarchitecture and fracture risk. In 74 NF1 patients (48 females, 26 males, age 41 ± 12), we measured TBS and investigated clinical stage, lifestyle, vitamin D, serum bone turnover markers, vertebral and femoral BMD. A homogenous cohort of 61 healthy subjects was used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
15
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 25 publications
(45 reference statements)
4
15
1
Order By: Relevance
“…TBS was found lower in NF1 individuals without differences between sexes. As expected, 25(OH)D levels and BMD in hip and spine were also lower in NF1 subjects compared to healthy controls [ 423 ]. In the NF1 group, there was an evident association between serum vitamin D concentrations and the number of dermal neurofibromas, confirming previously reported data [ 417 ].…”
Section: Vitamin D and Neurofibromatosissupporting
confidence: 75%
See 2 more Smart Citations
“…TBS was found lower in NF1 individuals without differences between sexes. As expected, 25(OH)D levels and BMD in hip and spine were also lower in NF1 subjects compared to healthy controls [ 423 ]. In the NF1 group, there was an evident association between serum vitamin D concentrations and the number of dermal neurofibromas, confirming previously reported data [ 417 ].…”
Section: Vitamin D and Neurofibromatosissupporting
confidence: 75%
“…In a recent investigation, Filopanti and colleagues proposed the trabecular bone score (TBS) as a tool for the measurement of bone microarchitecture and fracture risk in people with NF1 [ 423 ]. The authors determined vitamin D levels, vertebral and femoral BMD and TBS in 74 Italians with NF1 (26 males and 48 females) using a cohort of 61 voluntary healthy subjects (16 males and 45 females) as control group [ 423 ]. TBS was found lower in NF1 individuals without differences between sexes.…”
Section: Vitamin D and Neurofibromatosismentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, NF1 patients reported a signi cant reduction in sun exposure compared to control subjects in the current study. Nonetheless, in vitro studies on skin samples might investigate the presence of a derangement of vitamin D production and metabolism in NF1 patients [35].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that children with CPT are usually associated with neuro bromatosis type 1 (NF1), a disorder in which there is a loss of function of the NF1 gene, and CPT is also a rare manifestation of NF1 [8,9]. During skeletal development, the deletion of the NF1 gene decreases the level of bone metabolism, and children's bones exhibit excessive catabolic and anabolic de ciencies with a decreased level of 25-hydroxyvitamin D3 .…”
Section: Introductionmentioning
confidence: 99%